1998
DOI: 10.1002/(sici)1097-4636(19980905)41:3<504::aid-jbm22>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate induction by sol‐gel‐derived titania coatings on titanium substrates in vitro

Abstract: Titanium and its alloys are used widely in the manufacture of orthopedic and dental implants. Sol-gelprepared titania is able to stimulate bone-like apatite formation in in vitro and in vivo cultures. These materials can be used, for example, as coatings on dental and orthopedic implants. However, the processes that lead to apatite formation are not fully understood. In this study different kinds of titania coatings on commercially pure titanium (c.p. Ti) were tested for apatite-forming ability. The rate of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 0 publications
2
86
0
Order By: Relevance
“…On the other hand, Peltola et al 3),6),9), 19) indicated that the structure of titania film surfaces on the nanometer scale is of importance for the in vitro apatite-forming ability. From our results (Table 2), the nanometer-scale surface roughness (Ra), maximal roughness height between a peak and a valley (P-V), and root mean square roughness (RMS) did not change after UV irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Peltola et al 3),6),9), 19) indicated that the structure of titania film surfaces on the nanometer scale is of importance for the in vitro apatite-forming ability. From our results (Table 2), the nanometer-scale surface roughness (Ra), maximal roughness height between a peak and a valley (P-V), and root mean square roughness (RMS) did not change after UV irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, Ti-based materials cannot bond directly to human bone tissue with chemical interactions, since they are not bioactive. In order to improve their surface properties and achieve superior bioactivity, several methods have been developed such as chemical treatment with H2O2, 1) sol-gel coating of titania layers, 2), 3) and the anodic polarization technique. 4) It was confirmed that bone-like apatite layers were deposited on titania film substrates in Kokubo's simulated body fluid (SBF).…”
Section: Introductionmentioning
confidence: 99%
“…4). After implantation, the preferential dissolution of b-TCP phase would result in functionally gradient porosity for bone ingrowth [903]. HA/zirconia-graded biocomposites were fabricated to enhance the mechanical properties of HA while retaining its bone bonding property [791].…”
Section: Functionally Graded Biocompositesmentioning
confidence: 99%
“…Moreover, materials prepared by the sol-gel process have shown to be more bioactive than those of the same composition prepared by other methods, with improved calcium and phosphate precipitation onto the implant surface [11,12].…”
Section: Introductionmentioning
confidence: 99%